Fotoperiodismo en la era digital: análisis comparativo del rol del fotoperiodista - Cabrera Espinoza, Josthyn Jaime (Machala, 2020)
At present, the phenomenon of mobile technology and the reduction of the costs of photographic and technological equipment have allowed any citizen to become a potential image creator, a situation that has caused serious conflicts at a professional level regarding the value of the photojournalist role, who a few years ago was considered with a degree of exclusivity in the informative image. This research had as main objective to compare the current panorama of the professional in photojournalism in the digital environment at local and national level, establishing as specific objectives to characterize the role of the photojournalist in the digital era, analyze the current situation experienced by photojournalism professionals in the current digital context and finally determine the challenges and opportunities of photojournalism in this context. To solve these questions, a qualitative methodology is applied, through the application of in-depth interviews with photojournalist professionals both nationally and locally. From the analysis of their responses, the results are shown that show that the photojournalist must adapt to technology and continue training, catching up, that is, the photographer must be curious so that he can perform quality work and expand new horizons with networks social, ensuring the preservation of the trade and the implementation of new work formulas.
En la actualidad el fenómeno de la tecnología móvil y la reducción de los costes de equipos fotográficos y tecnológicos han permitido que cualquier ciudadano se transforme en un potencial creador de imágenes, situación que ha ocasionando serios conflictos a nivel profesional referentes al valor del rol fotoperiodista, quien hace algunos años atrás se consideraba con un grado de exclusividad en la imagen informativa. Esta investigación tuvo como objetivo principal comparar el panorama actual del profesional en el fotoperiodismo en el entorno digital a nivel local y nacional, estableciéndose como objetivos específicos el caracterizar el rol del fotoperiodista en la era digital, analizar la situación actual que viven los profesionales del fotoperiodismo en el actual contexto digital y por último determinar los retos y oportunidades del fotoperiodismo en este contexto. Para resolver estas cuestiones se aplica una metodología cualitativa, a través de la aplicación de entrevistas en profundidad a profesionales fotoperiodistas tanto a nivel nacional como local. Del análisis de sus respuestas se extrae los resultados que muestran que el fotoperiodista debe adaptarse a la tecnología y seguir capacitándose, poniéndose al día es decir el fotógrafo debe ser curioso para de esa manera poder realizar un trabajo de calidad y expandir nuevos horizontes con las redes sociales, asegurando la preservación del oficio y la implementación de nuevas fórmulas de trabajo.
Keywords: FOTOPERIODISMO; ERA DIGITAL; RED SOCIAL; FOTOGRAFIA